1989
DOI: 10.1007/bf00637392
|View full text |Cite
|
Sign up to set email alerts
|

Serum and urinary markers of skeletal muscle tissue damage after weight lifting exercise

Abstract: The purpose of this study was to determine whether high intensity weight lifting exercise produces elevations of urinary 3-methylhistidine (3-MH), serum creatine kinase activity (CK), and serum myoglobin concentration (MY), and whether trained weight lifters differed in such responses when compared to a group of untrained subjects. Ten experienced male weight lifters (EWL) and seven untrained male subjects (IWL) performed three sets of six weight lifting exercises at 70%-80% of 1 RM. All subjects consumed a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
6

Year Published

1990
1990
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 15 publications
2
21
0
6
Order By: Relevance
“…Perceived soreness was increased above the baseline value following muscle-damaging exercise, with peak values occurring at 48 h. These findings mirror those of previous research, which has demonstrated prolonged increases in muscle soreness peaking between 24 h and 72 h (Newham et al 1983;Jones et al 1987;Newham et al, 1987; Cleak and Eston 1992;Nosaka and Clarkson 1997;Whitehead et al 1998), indicating damage and inflammation of non-contractile connective tissue The changes in CK were consistent with those observed following weightlifting (Paul et al 1989;Byrne and Eston 2002b), plyometric exercise (Horita et al 1999) and downhill running (Eston et al 1996) with values peaking at 48 h after damaging exercise. This is in contrast to the temporal pattern associated with high force eccentric exercise, which demonstrates more of a delayed response peaking at 4 -7 days after exercise Clarkson et al 1992;Byrne et al 2001) Maximal intensity exercise performance…”
Section: Evidence Of Muscle Damagesupporting
confidence: 90%
See 1 more Smart Citation
“…Perceived soreness was increased above the baseline value following muscle-damaging exercise, with peak values occurring at 48 h. These findings mirror those of previous research, which has demonstrated prolonged increases in muscle soreness peaking between 24 h and 72 h (Newham et al 1983;Jones et al 1987;Newham et al, 1987; Cleak and Eston 1992;Nosaka and Clarkson 1997;Whitehead et al 1998), indicating damage and inflammation of non-contractile connective tissue The changes in CK were consistent with those observed following weightlifting (Paul et al 1989;Byrne and Eston 2002b), plyometric exercise (Horita et al 1999) and downhill running (Eston et al 1996) with values peaking at 48 h after damaging exercise. This is in contrast to the temporal pattern associated with high force eccentric exercise, which demonstrates more of a delayed response peaking at 4 -7 days after exercise Clarkson et al 1992;Byrne et al 2001) Maximal intensity exercise performance…”
Section: Evidence Of Muscle Damagesupporting
confidence: 90%
“…Exercise-induced muscle damage (EIMD) is a common occurrence following activities with a high eccentric component, such as resistance training, plyometrics, distance running and prolonged, intermittent shuttle running (Sherman et al 1984;Paul et al 1989;Chambers et al 1998;Avela et al 1999;Horita et al 1999; Thompson et al 1999;Byrne and Eston 2002a, b;Byrne et al 2004). Of the many symptoms that accompany muscle damage, including soreness, increased blood myofibre proteins, swelling and decreased range of motion, perhaps the most significant factor is the longlasting impairment of muscle function.…”
Section: Introductionmentioning
confidence: 97%
“…It is difficult to ascertain whether observed changes in a selected analyte are negatively affected by this change. A study [255] investigating the excretion of the muscle damage marker 3-methylhistidine following resistance exercises showed a decrease in concentration in conjunction with an increase in serum myoglobin and creatine kinase (CK). It is unusual that a change in muscle tissue damage occurs without skeletal muscle protein degradation.…”
Section: Creatininementioning
confidence: 99%
“…Exercise Induced Muscle Damage (EIMD) is a well-known phenomenon in exercise literature follows unaccustomed eccentric activities [4,5] like plyometric, long distance running and resistance activities [6][7][8][9][10][11][12][13][14]. Eccentric exercise-induced muscle damage is indicated by prolonged decreases in muscle strength range of motion (ROM), swelling, delayed onset muscle soreness (DOMS), increased muscle proteins, CK in the blood [15].…”
mentioning
confidence: 99%